SNP rs615552 and lncRNA CDKN2B-AS1 influence brain cancer pathogenesis through multi-omic mechanisms - Zheng Ye; Jiaqi Yuan; Qianbei Yi; Peng Xu; Wenbin Liu (Scientific Reports)
Abstract Brain cancer represents a complex disease influenced by a multitude of genetic and epigenetic factors. This study aims to elucidate the role of specific single nucleotide polymorphisms (SNPs) and long non-coding RNAs (lncRNAs) in the pathogenesis of brain cancer, employing a multi-omics approach. We conducted extensive eQTL, mQTL, haQTL, sQTL, and caQTL analyses to identify genetic variants and lncRNAs associated with brain cancer. Integration with GWAS-GWAS colocalization analysis provided insights into shared genetic mechanisms with other diseases. We further investigated copy number variation (CNV) and methylation status in relation to gene expression, and their prognostic implications in different brain cancer subtypes. SNP rs615552_AL359922.1 exhibited significant colocalization with key genes CDKN2A, CDKN2B, and CDKN2B-AS1, implicating its role in the regulation of gene expression. The long non-coding RNA CDKN2B-AS1 demonstrated both co-occurrence and co-expression with CDKN2A and CDKN2B, suggesting a coordinated regulatory mechanism among these genes. TERT emerged as a gene with shared susceptibility across brain cancer and other diseases, indicating a common genetic pathway. Methylation sites associated with mQTL, such as cg03935379 (TERT) and cg14069088 (CDKN2A), were identified as independent prognostic factors for lower-grade glioma (LGG), but not for glioblastoma multiforme (GBM). Bulk RNA-seq, spatial, and single-cell transcriptomic analyses revealed that CDKN2B-AS1 is predominantly expressed in malignant and dendritic cells (DCs), and is associated with DNA repair pathways in malignant cells and antigen presentation genes in DCs. This study offers a comprehensive perspective on the genetic and molecular factors influencing brain cancer. The results highlight the intricate nature of gene regulation in cancer and suggest the potential of CDKN2B-AS1 as a key regulator of immune responses and tumor suppressor genes. The SNP rs615552_AL359922.1 represents a significant pathogenic SNP for brain cancer. The identification of shared genetic mechanisms, particularly involving TERT, with other diseases points to new opportunities for developing therapeutic targets and diagnostic tools. Future research should focus on functional validation and the investigation of environmental interactions to fully leverage these findings for advancing brain cancer management.